Data conversion handbook - Kester, Walt.; Analog Devices, inc. (Amsterdam ; Boston : Elsevier : Newnes, 2005)
This comprehensive handbook is a one-stop engineering reference. Covering data converter fundamentals, techniques, applications, and beginning with the basic theoretical elements necessary for a complete understanding of data converters, this reference covers all the latest advances in the field. This text describes in depth the theory behind and the practical design of data conversion circuits as well as describing the different architectures used in A/D and D/A converters. Details are provided on the design of high-speed ADCs, high accuracy DACs and ADCs, and sample-and-hold amplifiers. Also, this reference covers voltage sources and current reference, noise-shaping coding, and sigma-delta converters, and much more. The books 900-plus pages are packed with design information and application circuits, including guidelines on selecting the most suitable converters for particular applications. Youll find the very latest information on: Data converter fundamentals, such as key specifications, noise, sampling, and testing Architectures and processes, including SAR, flash, pipelined, folding, and more Practical hardware design techniques for mixed-signal systems, such as driving ADCs, buffering DAC outputs, sampling clocks, layout, interfacing, support circuits, and tools. Data converter applications dealing with precision measurement, data acquisition, audio, display, DDS, software radio and many more. The accompanying CD-ROM provides software tools for testing and analyzing data converters as well as a searchable pdf version of the text. * Brings together a huge amount of information impossible to locate elsewhere. * Many recent advances in converter technology simply aren't covered in any other book. * A must-have design reference for any electronics design engineer or technician.
1. Fundamentals of Sampled Data Systems -- Coding and Quantizing -- DAC/ADC Ideal Static Transfer Functions -- Sampling Theory -- Data Converter AC errors and specifications -- 2. DAC Architectures and Origins -- Kelvin Divider -- String DACs -- R/2R DACs -- Segmented DACs -- Capacitor DACs -- Multiplying DACs -- Interpolating DACs -- Deglitching DAC outputs -- PWM DACs -- Sigma-Delta DACs -- Video DACs with lookup tables -- Digital potentiometers -- MicroDACs -- LogDACs -- 3. ADC Architectures and origins -- Low speed -- High speed -- Sigma-Delta -- 4. Data Converter Process Technology -- 5. Testing Data Converters -- 6. Interfacing to ADCs and DACs -- 7. Data Conversion Support Circuits -- Sample-and-hold circuits -- Voltage references -- Analog switches and multiplexers -- 8. Applications -- Precision measurement and sensor conditioning -- Data acquisition subsystems -- Multichannel systems and multiplexing -- Data distribution systems using multiple DACs -- Digital pot applications -- Display electronics -- Audio -- Video -- Software radio and IF sampling -- Higher levels of integration -- DDS -- 9. Hardware Design Techniques for Mixed-Signal Systems -- Passive components -- Printed circuit board design issues -- Layout -- "Smart" Partitioning -- Grounding mixed signal devices -- Digital isolation techniques -- Filtering switching supply outputs -- Data converter overvoltage protection -- Thermal considerations -- EMI/RFI considerations -- Logic considerations -- Simulation and IBIS models -- Prototyping -- Evaluation Boards -- Appendix -- Index.
Includes bibliographical references and index.
Keywords: Digital-to-analog converters -- Handbooks, manuals, etc; Analog-to-digital converters -- Handbooks, manuals, etc; Electronic circuit design -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc